Determinants Of Stock Liquidity During COVID-19: Evidence From Indonesian Listed Firms - Gushendri, Adzra Helga Engrasia; Yunita, Irni (International Journal of Science, Technology & Management, 2024)
The COVID-19 pandemic has heightened awareness among Indonesian citizens regarding the significance of investing. The increased market capitalization of the IHSG has contributed to enhanced stock liquidity during this period. Prospective investors assess both internal and external factors of companies to make informed investment decisions, aligning their capital allocation with the perceived potential of the target firms. The objective of this research is to empirically analyze the determinants of stock liquidity, including firm size, profitability, leverage, firm growth, inflation, and dividend policy, focusing on non-financial companies listed in Indonesia during the COVID-19 period. The empirical results indicate a negative and significant relationship between stock liquidity and company size, profitability, leverage, growth, inflation, and dividend policy among non-financial firms listed on the IDX30 for the period February to July 2023.